Herbal Choice: Uncovering the Natural Medicine Consumption Patterns of Indonesians - Shine Pintor Siolemba Patiro; Prisila Damayanti; Hendrian Hendrian; Minrohayati Minrohayati (Celebes Scholar pg, 2026)
This study examines consumer perceptions of products containing natural ingredients using the theory of planned behavior as a theoretical basis. As an antecedent of Attitudes, subjective norms, and perceived behavioral control were examined. This study used price fairness and ease of use as the indicators. The online survey was conducted using the Google Forms platform, involving residents in five major Indonesian cities: Jakarta, Surabaya, Semarang, Medan, and Makassar. Overall, 305 respondents participated. Valid observations were collected for further analysis. The analysis technique for this research used a structural equation model. based on maximum likelihood to test the research hypothesis and found that price fairness and ease of use have a positive effect on attitudes, subjective norms, and perceived behavioral control. In addition, intention to use is positively influenced by attitudes, subjective norms, and perceived behavioral control. behavioral control. This study contributes to the literature by demonstrating the explanatory power of behavioral control theory. planned in the context of natural medicinal products from the perspective of Indonesian society.